Terapi Kelompok Terapeutik Memperkuat Pencapaian Integritas Diri Lansia: Therapeutic Group Therapy Strengthens the Achievement of Self-Integrity in the Elderly - Wawo, Balbina Antonelda Marled; Risha, Elizabeth; Sisilia, Sisilia; Dwiliana, Dwiliana (Chakra Brahmanda Lentera Institute, 2025)
The increasing elderly population and the prevalence of degenerative diseases with residual symptoms require promotive efforts to maintain physical and mental health. Therapeutic Group Therapy (TGT) is considered effective in improving elderly self-integrity, but its scientific application is still limited. This community service project employed a quasi-experimental one-group posttest-only design involving 15 healthy elderly participants in Cawang Subdistrict, East Jakarta. The TGT intervention consisted of two sessions addressing adaptation to biological, sexual, and cognitive changes. Data on self-integrity achievement were collected using a questionnaire and analyzed descriptively. All participants achieved maximum self-integrity scores (>6) after the intervention. The elderly reported increased enthusiasm for life, improved self-confidence, reduced anxiety, and greater social engagement. These findings indicate that TGT is effective as a community-based intervention to enhance psychological and social well-being in the elderly, consistent with previous research. TGT is recommended as a routine intervention model in community elderly health programs to improve quality of life and prevent psychological problems.